Microbiota Gut–Brain Axis in Ischemic Stroke: A Narrative Review with a Focus about the Relationship with Inflammatory Bowel Disease - Sinagra, Emanuele; Pellegatta, Gaia; Guarnotta, Valentina; Maida, Marcello; Rossi, Francesca; Conoscenti, Giuseppe; Pallio, Socrate; Alloro, Rita; Raimondo, Dario; Pace, Fabio; Anderloni, Andrea (Life (Basel, Switzerland), 2021)
The gut microbiota is emerging as an important player in neurodevelopment and aging as well as in brain diseases including stroke, Alzheimer’s disease, and Parkinson’s disease. The complex interplay between gut microbiota and the brain, and vice versa, has recently become not only the focus of neuroscience, but also the starting point for research regarding many diseases such as inflammatory bowel diseases (IBD). The bi-directional interaction between gut microbiota and the brain is not completely understood. The aim of this review is to sum up the evidencesconcerningthe role of the gut–brain microbiota axis in ischemic stroke and to highlight the more recent evidences about the potential role of the gut–brain microbiota axis in the interaction between inflammatory bowel disease and ischemic stroke.